Managerial Characteristics and Investment Efficiency: Evidence from Indonesian Listed Companies - Butar-Butar, Sansaloni (Jurnal Dinamika Akuntansi dan Bisnis, 2022)
This study examines the effect of managerial characteristics on investment efficiency. More specifically managerial capabilities, reputation and its interaction effect are expected to increase investment efficiency. For the test of hypothesis, firms were selected from Indonesia Stock Exchange from 2015-2019. The results show that reputation is not significantly associated with investment efficiency. Meanwhile, managerial ability (proxied by MBA/MM degree) is negatively related to investment efficiency at a significance level of 1%. The findings show that companies run by managers with good skills and knowledge tend to be less efficient. In addition, the interaction variable is positively related to investment efficiency at a significance level of 1%. Prior to the inclusion of interaction variable, the result shows that firms with high managerial reputation are more likely to manage assets efficiently which leads to higher investment efficiency. Managerial skills are either insignificantly associated or negatively associated with investment efficiency. When the interaction variable is included into regression model, the relationship between managerial reputation and investment efficiency becomes insignificant but managerial ability turns out to be highly significant. The practical implication of this study is that public companies in Indonesia should consider more on managerial reputation rather than their educational degree.